Clinical study of cefpirome in treating complicated urinary tract infection caused by Enterococcus faecalis - Matsumoto, Tetsuro (Japanese Journal of Chemotherapy, 2000)
We studied the bacteriological effect and resistances to cefpirome (CPR) in the treatment of complicated urinary tract infection caused by Enterococcus faecalis over the 5 years from 1994 to 1998. E. faecalis was isolated in 68 of 129 subjects (52.7%) in whom clinical efficacy was analyzable. Monomicrobial infection accounted for 33.8%(23/68) and polymicrobial infection for 66.2%(45/68). In terms of clinical efficacy in E. faecalis-isolated subjects, cefpirome was markedly effective in 21 subjects, effective in 36, and no response or ineffective in 11. Efficacy was 83.8%. Efficacy in monomicrobial infection was 87.0% and that in polymicrobial infection was 82.2%. Efficacy related catheter was 73.7% with use and 87.8% without, indicating a favorable outcome in either case. The efficacy of CPR in subjects in whom E. faecalis was not detected was 82.0%, comparable to E. faecalis-isolated subjects. No particular problem was seen in adverse subjective or objective adverse effects. In the MIC distribution of CPR against E. faecalis by isolation chronology, MIC50was 6.25 or 12.5μg/mL whereas MIC90 was 25 or 50μg/mL findings similar to those for strains isolated during from 1985 to 1988. For MIC100, 200μg/mL was the highest recorded before 1990, indicating no trend toward resistance. CPR is the first cephem medicinal product approval for use against E. faecalis, which has thus far shown no problem such as decreased efficacy or the development of resistance, demonstrating its usefulness.